Spatiotemporal evolution patterns and driving factors of arable land in Huaihai Economic Zone, China - Wang, Peijun; Lin, Ziqi; Wang, Jing; Yang, Yali; Mu, Shouguo (Frontiers in Environmental Science, 2023)
The Huaihai Economic Zone (HEZ) has excellent topographic and climatic conditions and is one of China's major grain production areas. Identifying the spatio-temporal evolution patterns of arable land and the driving factors can provide references for protecting arable land, optimizing land use layout, and developing ecological economics in HEZ. In this paper, we analyze the spatiotemporal evolution patterns and detect the driving factors of arable land evolution. The results show that:(1) kernel density distribution of the arable land in HEZ was roughly the same from 2005 to 2020, but the density showed a downward trend with time. (2) The distribution of arable land in HEZ was less in the Northeast and more in the Southwest, with growth in the preliminary stage and negative growth in the metaphase and last phase. (3) There was a significant positive spatial correlation of the arable land distribution in HEZ. The main local cluster types are the "high-high" and "low-low" clusters, and the distribution characteristics were similar to the kernel density of arable land. (4) The change of arable land in HEZ from 2005 to 2020 is dominated by the transfer out of land types, mainly to grassland and construction land. (5) The main driving factors affecting the spatial distribution of arable land in HEZ were traffic accessibility, air temperature, precipitation, elevation, and slope. The secondary driving factors were land use and soil type. At the same time, population and GDP have also become the main driving factors over time. (6) The factors bi-enhance after the interaction. In the future, all cities in HEZ should focus on balancing grain production security and economic benefits. The administration departments should increase the consolidation and reclamation of destroyed arable land, introduce incentive policies for agricultural production, and pay more attention to the interactive effects of traffic accessibility, population, and GDP, to protect the arable land in a more targeted manner.